Antimicrobial resistance of bacterial strains isolated from avian cellulitis - Santos, Milena Mendonça dos (2014)
Avian cellulitis is an inflammatory process in the subcutaneous tissue, mainly located in the abdomen and thighs. This problem is commonly observed in poultry at slaughter and it is considered one of the major causes of condemnation of carcasses in Brazil. The aim of this study was to perform the microbial isolation of lesions of avian cellulitis from a processing plant located in the State of Goiás in order to analyze antimicrobial resistance by antibiogram test and to detect resistance genes by polymerase chain reaction. A total of 25 samples of avian cellulitis lesions were analyzed, from which 30 bacterial strains were isolated. There were eleven (44%) strains of Escherichia coli, nine (36%) strains of Staphylococcus epidermidis, seven (28%) strains of Proteus mirabilis and three (12%) strains of Manheimiahaemolytica. The antibiogram test showed that all strains were resistant to at least one antimicrobial. The gene of antimicrobial resistance tetB was detected in E. coli, S. epidermidis and P. mirabilis strains, and was the most frequently observed gene. The gene of antimicrobial resistance Sul1 was detected in all bacterial species, while tetA was found in E. coli and S. epidermidis strains, SHV in E. coli strains, S. epidermidis and P. mirabilis,and cat1 in one P. mirabilis strain. The results suggest a potential public health hazard due to the ability of these microorganisms to transmit antimicrobial resistancegenes to other microorganisms present in the intestinal tract of humans and animals, which may affect clinical-medical usage of these drugs.